Análisis para el diseño de una Aplicación Móvil para el control de Banano en las empresas Supervisoras de la Gestión de Calidad. - Cornejo Ávila, Eder Leandro (2022)
This case study proposes a mobile application for the control of banana management in quality supervisory companies, through research and also conducting interviews with experts on programming, developing an in-depth analysis of whether it is necessary to carry out or implement the mobile application, therefore Research will be carried out on how supervisors and quality inspectors manage during the harvest and packaging phases in order to complement the use of mobile technologies based on the information collected.